Arabic Language Learning Using the Sharaful Qur’an Guidebook: A Case Study in an Islamic Learning Community - Muhamad Fathoni; Cahya Edi Setyawan; Yumna (UIN Raden Mas Said Surakarta, 2026)
Community based Arabic language learning remains underrepresented in academic documentation, despite its strategic role in strengthening religious literacy and adolescents’ linguistic competence. This article aims to analyze the practice of Arabic language instruction utilizing the Sharaful Qur’an guidebook as the primary instructional framework. The study employs a descriptive qualitative approach with a case study design. Data were collected through observation, documentation, and analysis of instructional materials, and subsequently analyzed using data reduction, thematic coding, and triangulation techniques. The findings indicate that the learning process is conducted in small groups, focusing on reading, copying, and reinforcing morphological rules (sharf) to support comprehension of Qur’anic texts. The use of the guidebook functions not only as a source of content but also as a pedagogical tool that structures the learning sequence, ensures consistency in content delivery, and facilitates systematic instructional scaffolding. This model contributes to a more structured learning process and demonstrates a relatively high degree of replicability in community based contexts. However, challenges arise from participants’ heterogeneous initial abilities and the lack of standardized assessment systems. These findings highlight the contribution of guidebook-based models as a pedagogical alternative in the development of Arabic language learning in non-formal settings.